2014
DOI: 10.1021/bi401078b
|View full text |Cite
|
Sign up to set email alerts
|

How Hydrogen Peroxide Is Metabolized by Oxidized Cytochrome c Oxidase

Abstract: In the absence of external electron donors, oxidized bovine cytochrome c oxidase (CcO) exhibits the ability to decompose excess H2O2. Depending on the concentration of peroxide, two mechanisms of degradation were identified. At submillimolar peroxide concentrations, decomposition proceeds with virtually no production of superoxide and oxygen. In contrast, in the millimolar H2O2 concentration range, CcO generates superoxide from peroxide. At submillimolar concentrations, the decomposition of H2O2 occurs at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…A similar mechanism could take place at the level of the electron chain complexes upstream to the complex IV, which may account for the restoration of the mitochondrial function. We have suggested that molecules of hydrogen peroxide produced during the reoxidation of LMB by O 2 , 96,97 before being “transformed” into H 2 O by a large amount of catalase present in cells, could oxidize various metalloproteins 98,99 of the electron chain complexes “stuck” in a reduced state 24,25 . Such reoxidation could restore the capacity of the electron chain to be reduced again (by LMB or NADH).…”
Section: Discussionmentioning
confidence: 99%
“…A similar mechanism could take place at the level of the electron chain complexes upstream to the complex IV, which may account for the restoration of the mitochondrial function. We have suggested that molecules of hydrogen peroxide produced during the reoxidation of LMB by O 2 , 96,97 before being “transformed” into H 2 O by a large amount of catalase present in cells, could oxidize various metalloproteins 98,99 of the electron chain complexes “stuck” in a reduced state 24,25 . Such reoxidation could restore the capacity of the electron chain to be reduced again (by LMB or NADH).…”
Section: Discussionmentioning
confidence: 99%
“…Two molecules of O 2 •− are formed in the BNC and undergo dismutation into the new H 2 O 2 molecule [ 124 ]. At submillimolar concentrations of H 2 O 2 , its decomposition occurs at least at two sites: (i) the catalytic heme a 3 −Cu B center where H 2 O 2 is reduced to water via the P M and F states, and (ii) the surface-exposed lipid-based radicals generated due to the migration of radicals formed initially in the catalytic heme a 3 −Cu B center [ 125 ].…”
Section: Ros and Heme-copper Oxidasesmentioning
confidence: 99%
“…However, such a mechanism is irrelevant during CN intoxication as the electron chain is already reduced. We have recently proposed (Haouzi et al, 2018b) that molecules of hydrogen peroxide produced during the re-oxidation of LMB by O 2 (Schirmer et al, 2011;Wainwright and Amaral, 2005), before being "transformed" into H 2 O by the large amount of catalase present in cells, could re-oxidize the metallo-proteins (Jancura et al, 2014;Jü nemann et al, 2000) of the electron chain complexes "stuck" in a reduced state. Such re-oxidation could restore the capacity of the electron chain to be reduced again (by LMB or NADH) and allow electrons to flow at least up to the complex III.…”
Section: Treatment Of Life-threatening Cn Intoxication By Mb: Mechanisms Of Actionmentioning
confidence: 99%